Study of dispersed additives for the formation of polymer composite materials to increase the performance characteristics of friction units of transport vehicles - Yakushchenko, S. V.; Brailo, M. V.; Sapronov, O. O.; Zinchenko, S. M. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2022)
The scientific paper presents the technological aspects of modifying the ED-20 epoxy oligomer with carbon-containing additives to improve the thermophysical characteristics of nanocomposite materials and functional protective coatings based on them. The dynamics of the dependence of carbon nanotube content on the thermophysical properties of nanocomposites has been studied. Materials with improved thermal conductivity values are proposed for the formation of adhesives or functional coatings for the repair of gas equipment. The developed nanocomposites containing carbon nanotubes with the content of q = 0.075–0.100 pts.wt. per 100 pts.wt. of ED-20 epoxy oligomer are characterized by improved thermal conductivity λ = 0.40–0.58 W/m∙K. An additional comparison of the structure of the developed nanocomposites and the calculated value of the activation energy allows us to state that a 2.0–2.7 times improvement in the thermophysical characteristics is associated with the resistance of the physicochemical bonds to the effects of temperature due to the active chemical and physical effects of the nanoadditive.